ANALYSIS OF INDIGENOUS USES AND AVAILABLE PROCESSING TECHNOLOGIES OF PEARL-MILLET AMONG RURAL WOMEN IN JIGAWA STATE, NIGERIA - Bello, O. G.; Akinyemi, M.; Abdulrahman, O. L.; Shuaib, S. B.; Zanfara, M. I.; Hussaini, A. (FUDMA JOURNAL OF SCIENCES, 2023)
The study examined the indigenous uses and available processing technologies on pearl-millet among women in Jigawa State, Nigeria. A multistage sampling technique was used to select one hundred and sixty women millet processors for the study. Majority were married (73.1%), Muslims (94.3%) and with no formal education (60.0%). About 96.9% were within the age range of 21-50 years (M=40 years), mean household size and monthly income are 9 persons and N7, 069.18k respectively. About 98.0% sourced labor for millet processing from the family. Funds for business were mostly through borrowing from members of family/relatives (48.8%) and cooperative movement (38.8%). Secondary occupations is either trading (49.4%) or farming (46.9%). Larger percentage (95.0%) of therespondents belongs to one social group or the other. Most available millet processing technologies are soaking/cooking and traditional/bioprocessing (98.1%) while about 41.0% used the thermal improved processing technique. Most uses were; production of Fura, Tuwo, Kunu (98.1%) and closely followed by Ogi, Koko or Akamu (96.9%) among others. Major constraints were; inadequate capital and storage facilities (97.5%). This was followed by nomadic Fulani invasion of farm, lack of improved processing skills, insect pest infestation, processing equipment and extension contact (93.8%).Advocacy (75.6%) on uses of millet is another. Main source of awareness is family/friends/neighbors (88.1%). The study recommended that government should strengthen the extension service delivery by employing more personnel with adequate training to reduce the gap of processors and extension agent contact. Improved variety with good processing value compactable with the socio-cultural background of the
Keywords: Women, Processing, Technologies, Economic, Utilization and Jigawa State